Bond strength of composite resin/universal adhesive to dentin submitted to radiotherapy - Fabiana De Goes Paiola; Aline Evangelista Souza-Gabriel; Vitoria Leite Paschoini; Alexandra Mussolino de Queiroz; Antônio Miranda Cruz-Filho (Universidad de Concepción., 2023)
Aim: To evaluate the bond strength of a universal adhesive system to dentin submitted to radiotherapy. Materials and Methods: Sixty extracted human teeth were divided into two groups (n = 30): without radiotherapy (control); with radiotherapy, according to the adhesive protocol (n=15): ER-etch-and-rinse (acid + Single Bond Uni-versal); SE-self-etch (Single Bond Universal). The analyzes were shear bond strength (SBS) (n=10), failure pattern (n=10) and scanning electron microscopy (n=5). Data was analyzed by a two-way ANOVA (α =0.05). Results: The radiotherapy decreased SBS of the restorative material to dentin (p<0.0001). The ER protocol provided lower bond strength values (p<0.001). The predominant type of fracture without radiotherapy was mixed (SE), cohesive to the material (ER). Both protocols presented adhesive failures with radiotherapy. Teeth had a hybrid layer and long resin tags (without radiotherapy) and few tags (with radiotherapy). Conclusions: The SE adhesive mode favors the shear bond strength of resin to dentin in teeth submitted to radiotherapy.